Sectoral growth linkages of agricultural sector: Implications for food security in Pakistan - Hafiz Asim; Muhammad Akbar (Agricultural Economics (AGRICECON), 2019)
Does the growth in non-agricultural sectors spill over to the agricultural sector of an economy? There is limited evidence available on the issue for the developing world, especially for Pakistan which has undergone large structural changes since its independence. This study examined the impact of sectoral growth linkages on agricultural output of Pakistan for the period of 1960-2016. We have estimated an econometric model which incorporates inter-sectoral linkages of Pakistan economy using a Vector Error Correction Model (VECM). Our analysis revealed that the economy of Pakistan has shifted from an agricultural dominant economy to services-based economy during the past six decades. Results of VECM show that the industrial sector has a negative impact on the performance of agricultural output whereas services sector is influencing the output of agriculture sector positively in the long run. Short run results show that industrial sector is affecting the performance of agricultural output positively whereas services sector is influencing the output of agriculture sector negatively. Negative impacts of industry in the long run and services in the short run imply that agricultural sector should be given its due share in public investment and the role of middle man should be minimised at the time of sale of agricultural production in the markets.